OPTIMASI PENJUALAN GULA AREN DI KABUPATEN LEBAK MENGGUNAKAN METODE SIMPLEKS: (STUDI KASUS UMKM GULA AREN HARIANG) - Nayla Firlitha; Aliudin Aliudin; Ardelia Nahdah Nurnudiya; Zahra Syifa’H (CV. Denasya Smart Publisher, 2025)
UMKM Gula Aren Hariang in Lebak Regency faces major challenges in optimizing its sales strategy due to limitations in capital, time, and production capacity. This study aims to formulate an optimal sales strategy using the Simplex method, a linear programming approach proven effective in efficiently allocating resources. Data were collected from sales volume, production costs, and working hours across three main product variants: powdered palm sugar, molded palm sugar, and liquid palm sugar. Using the POM-QM application, the optimal solution was found by producing 300 units of powdered palm sugar, 200 units of molded palm sugar, and 180 units of liquid palm sugar, generating a total revenue of IDR 23,800,000 and a monthly profit margin of IDR 3,960,000. The analysis reveals that limited capital is the primary constraint to increasing production, even though working time capacity remains underutilized. This study recommends increasing capital as a long-term strategy to scale up production capacity and enhance the economic contribution of palm sugar UMKM to both the local community and the national economy. The Simplex method has proven to offer a practical, data-driven decision-making framework that can be effectively applied by UMKM actors to improve competitiveness in an increasingly dynamic market.